Coordination of Fishery PPNS under Article 73(3) with POM AL Investigators under the New Criminal Procedure Code (Article 7) - Abdul Hayy Nasution; Abdul Halim; Ali Sati Rangkuti (Universitas Islam Sultan Agung, 2026)
Civil Servant Investigators (Penyidik Pegawai Negeri Sipil / PPNS) under Article 7 paragraph (5) of Law Number 20 of 2025 concerning the Criminal Procedure Code stipulates that coordination and supervision as referred to in paragraphs (3) and (4) shall not apply to investigators within the Office of the Attorney General of the Republic of Indonesia, the Corruption Eradication Commission, and the Indonesian Navy (Tentara Nasional Indonesia Angkatan Laut / TNI AL) in accordance with statutory provisions. This study analyzes the legal rationale for the exclusion of investigators from the Attorney General’s Office, the Corruption Eradication Commission, and the Indonesian Navy from the coordination and supervisory authority of the primary investigative body, namely the Indonesian National Police (Polri), as regulated under Article 7 paragraphs (3) and (4) of Law Number 20 of 2025 concerning the Criminal Procedure Code. Furthermore, this study examines the role of Fisheries PPNS and Naval Military Police investigators in conducting investigations into criminal offenses occurring within the Indonesian Exclusive Economic Zone (Zona Ekonomi Eksklusif Indonesia / ZEEI). This research employs a normative legal research method. The objective of this study is to examine the legal justification for the exemption of investigators from the Attorney General’s Office, the Corruption Eradication Commission, and the Indonesian Navy from Polri coordination and supervision as stipulated in Article 7 paragraphs (3) and (4) of Law Number 20 of 2025, as well as to analyze the role of Fisheries PPNS and Naval Military Police investigators in investigating criminal offenses within the ZEEI.